Araneophagic behavior of Gardena brevicollis Stål (Heteroptera: Reduviidae): Foraging on pre‐dispersal spiderlings in the spider's web. Issue 2 (17th April 2019) - Suzuki, Yuya
Abstract: Araneophagic behavior of an Emesinae assassin bug, Gardena brevicollis Stål (Hemiptera: Reduviidae) was observed in the field. The bug invaded a web of Acusilas coccineus Simon (Araneae: Araneidae) spiderlings and hunted five juvenile spiders. The bug showed stalking tactics to prey on spiders, whereas luring tactics, which have been reported in other Emesinae bugs, were not observed. To the best of my knowledge, the present study is the first report of araneophagy in the genus Gardena and the first report of araneophagic behavior in East Asian assassin bugs. Abstract : Araneophagic behavior of an Emesinae assassin bug, Gardena brevicollis Stål (Hemiptera: Reduviidae), was observed in the field. The bug invaded a web of spiderlings and used stalking tactics to hunt spiders. This is the first report of araneophagic behavior in East Asian assassin bugs.